2017
DOI: 10.22631/ijaep.v6i1.108
|View full text |Cite
|
Sign up to set email alerts
|

Time to failure and neuromuscular response to intermittent isometric exercise at different levels of vascular occlusion: a randomized crossover study

Abstract: ABSTRACT:Objectives: The purpose this study was to investigate the effects of different vascular occlusion levels (total occlusion (TO), partial occlusion (PO) or free flow (FF)) during intermittent isometric handgrip exercise (IIHE) on the time to failure (TF) and the recovery of the maximum voluntary isometric force (MVIF), median frequency (EMGFmed) and peak of EMG signal (EMGpeak) after task failure. Methods: Thirteen healthy men (21 ± 1.71 year) carried out an IIHE until the failure at 45% of MVIF with TO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 45 publications
(68 reference statements)
1
13
0
Order By: Relevance
“…As expected, FF condition presented a greater time to achieve the task failure, which may be associated to a markedly greater neural inhibition, induced by afferent sensory nerve fibers (groups III and IV) [31][32][33] . This postulate is in line with previous founds, which indicated that the magnitude of force reduction after the TF is strongly influenced by the exercise duration 5 . In fact, the slower force recovery after the TF observed in the task sustained for a long period (i.e., FF condition), may occur owing to deficiencies in the contractile apparatus, the membrane excitability, and excitation-contraction coupling 34 .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…As expected, FF condition presented a greater time to achieve the task failure, which may be associated to a markedly greater neural inhibition, induced by afferent sensory nerve fibers (groups III and IV) [31][32][33] . This postulate is in line with previous founds, which indicated that the magnitude of force reduction after the TF is strongly influenced by the exercise duration 5 . In fact, the slower force recovery after the TF observed in the task sustained for a long period (i.e., FF condition), may occur owing to deficiencies in the contractile apparatus, the membrane excitability, and excitation-contraction coupling 34 .…”
Section: Discussionsupporting
confidence: 93%
“…TOP is a measure that shows good reproducibility 20 and was determined according to the previous studies 5,20 . Briefly, the brachial artery blood flow of a dominant arm was detected by an ultrasound model SonoAceR3 (Samsung Medison -South Korea), by Power Doppler Technique -with 12 MHz linear transducers placed in the flexor crease of the elbow.…”
Section: Total Occlusion Pressure Determinationmentioning
confidence: 99%
See 3 more Smart Citations